Antibacterial polyacrylonitrile nanofibers produced by alkaline hydrolysis and chlorination - Aksoy, Oğuz Emre; Ateş, Büşra; Çerkez, İdris (Springer, 2017)
Antibacterial polyacrylonitrile (PAN) nanofibers were developed by alkaline hydrolysis and subsequent chlorination. It was shown that the hydrolyzed nanofibers could serve as an N-halamine precursor through chlorination of the amide groups obtained by partial hydrolysis of the nitrile groups. The hydrolysis conditions were optimized, so that sufficient chlorine for effective antibacterial activities could be obtained on the surfaces. The chemical and physical structural changes were well characterized with FTIR, TGA, DSC and SEM. It was found that even though the hydrolyzed nanofibers cyclized with ionic and free radical mechanisms, the chlorinated nanofibers cyclized with only free radical mechanism as evidenced by its higher onset of cyclization temperature. On the other hand, the hydrolysis and chlorination process significantly improved the mechanical properties of the nanofibers. Moreover, the chlorinated nanofibers showed potent antibacterial activities against S. aureus and E. coli with about 6 logs inactivation. The developed antibacterial PAN nanofibers possess great potential for use in various fields, medical industry in particular.
Keywords: [No Keywords]